A practical method of predicting wellbeing at work: the Wellbeing Process Tool - Williams, Gary; Smith, Andrew (Advances in Social Sciences Research Journal, 2018)
Research has shown that short measuring instruments (e.g. the Wellbeing Process Questionnaire – WPQ) can provide information about aspects of wellbeing. These measures have been shown to have good validity and reliability and can be used to assess multi-dimensional models (e.g. the Demands-Resources-Individual Effects model – DRIVE). The present article describes the practical application of the approach.